Solution and solid-state structure of the anion [Ag(2)[closo-CB(11)H(12)](4)](2-). - Fox, M; Mahon, M; Patmore, N; Weller, A (2002)
Addition of the carbene 1,3-dimesitylimidazol-2-ylidene (IMes) to a toluene solution of Ag[closo-CB(11)H(12)] results in the formation of the complex [(IMes)(2)Ag](2)[Ag(2)[closo-CB(11)H(12)](4)], the anionic component of which contains two silver(I) centers bridged by two carboranes in addition to one terminally bound carborane on each metal, in the solid-state. Comparison of the observed (11)B[(1)H] NMR chemical shifts of [(IMes)(2)Ag](2)[Ag(2)[closo-CB(11)H(12)](4)] or Ag[closo-CB(11)H(12)] with [NBu(4)][closo-CB(11)H(12)] in CD(2)Cl(2) demonstrates that the silver ion interacts significantly with the cage in solution. Theoretical investigations using the ab initio/GIAO/NMR method of [closo-CB(11)H(12)](-) and Na[closo-CB(11)H(12)] as model geometries for the silver salts support experimental evidence for these Ag...[BH] interactions in solution.